Regulation of microglial responses after pediatric traumatic brain injury: exploring the role of SHIP-1 - Chu, Erskine; Mychasiuk, Richelle; Green, Tabitha R. F.; Zamani, Akram; Dill, Larissa K.; Sharma, Rishabh; Raftery, April L.; Tsantikos, Evelyn; Hibbs, Margaret L.; Semple, Bridgette D. (Frontiers in Neuroscience, 2023)
Introduction Severe traumatic brain injury (TBI) is the world’s leading cause of permanent neurological disability in children. TBI-induced neurological deficits may be driven by neuroinflammation post-injury. Abnormal activity of SH2 domain-containing inositol 5′ phosphatase-1 (SHIP-1) has been associated with dysregulated immunological responses, but the role of SHIP-1 in the brain remains unclear. The current study investigated the immunoregulatory role of SHIP-1 in a mouse model of moderate–severe pediatric TBI. Methods SHIP-1+/− and SHIP-1−/− mice underwent experimental TBI or sham surgery at post-natal day 21. Brain gene expression was examined across a time course, and immunofluorescence staining was evaluated to determine cellular immune responses, alongside peripheral serum cytokine levels by immunoassays. Brain tissue volume loss was measured using volumetric analysis, and behavior changes both acutely and chronically post-injury. Results Acutely, inflammatory gene expression was elevated in the injured cortex alongside increased IBA-1 expression and altered microglial morphology; but to a similar extent in SHIP-1−/− mice and littermate SHIP-1+/− control mice. Similarly, the infiltration and activation of CD68-positive macrophages, and reactivity of GFAP-positive astrocytes, was increased after TBI but comparable between genotypes. TBI increased anxiety-like behavior acutely, whereas SHIP-1 deficiency alone reduced general locomotor activity. Chronically, at 12-weeks post-TBI, SHIP-1−/− mice exhibited reduced body weight and increased circulating cytokines. Pro-inflammatory gene expression in the injured hippocampus was also elevated in SHIP-1−/− mice; however, GFAP immunoreactivity at the injury site in TBI mice was lower. TBI induced a comparable loss of cortical and hippocampal tissue in both genotypes, while SHIP-1−/− mice showed reduced general activity and impaired working memory, independent of TBI. Conclusion Together, evidence does not support SHIP-1 as an essential regulator of brain microglial morphology, brain immune responses, or the extent of tissue damage after moderate–severe pediatric TBI in mice. However, our data suggest that reduced SHIP-1 activity induces a greater inflammatory response in the hippocampus chronically post-TBI, warranting further investigation.